2017
DOI: 10.1093/rpd/ncx244
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose TL Dosimetry of Reactor Neutrons

Abstract: Radiation dose was measured with set of TL dosimeters during checkout of neutron radiation hardness of the ORTEC preamplifier type 142A in the experiment at the MARIA nuclear reactor at the National Centre for Nuclear Research (NCBJ), Otwock-Świerk, Poland. Different types of LiF-based TL detectors have been used for measurements in order to evaluate neutron and non-neutron components of the radiation field in the reactor channel during exposure and to check their relevancy for dose measurements in the reactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The TLD700 results are not presented since their readout protocol was not suited for such high integrated dose levels. Further study on the TLD700 readout protocol are to be performed, based on work on reading procedures for high dose measurement with LiF:Mg,Cu,P detectors [10]- [12].…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…The TLD700 results are not presented since their readout protocol was not suited for such high integrated dose levels. Further study on the TLD700 readout protocol are to be performed, based on work on reading procedures for high dose measurement with LiF:Mg,Cu,P detectors [10]- [12].…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…The TLD700 results are not presented since their readout protocol was not suited for such high integrated dose levels. Further study on the TLD700 readout protocol are to be performed, based on work on reading procedures for high dose measurement with LiF:Mg,Cu,P detectors [10]- [12].…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…These materials were exposed to either gamma, neutron or electron beam irradiation and their use as dosimeters for high and very high radiation dose analyzed [37,38,43,[54][55][56][57]. Neutron detection from a nuclear reactor or neutron sources (such as Am-Be or 252 Cf) using thermoluminescence detectors has been a great challenge in radiation dosimetry, and several works have been devoted to investigating this process in the past [58,[63][64][65][66][67][68][69]. Particularly, interaction of thermal and epithermal neutron with matter has awakened special interest in some authors because a larger effective neutron capture cross-section than fast neutrons is found for some nuclides like 10 B and 6 Li [70][71][72].…”
Section: High and Very-high Radiation Dosementioning
confidence: 99%
“…In medical application, boron neutron capture therapy (BNCT) is a method for the treatment of brain tumors in which TLDs detectors can be used to determinate the gamma dose and evaluate the dose due to the charged particles generated in the thermal neutron interaction using consistent kerma factor [62,73]. On the other hand, Obryk et al [69] have mentioned that during the research of radiation damage to electronic components at the Maria research fission reactor, Poland, TL dosimetry using different kinds of MCP and MTS has been performed in order to evaluate the neutron and gamma components of the radiation field during exposure.…”
Section: High and Very-high Radiation Dosementioning
confidence: 99%
See 1 more Smart Citation